Identification and subsequent removal of an interference by FAIMS in the bioanalysis of dianicline in animal plasma. (September 2011) - Blackburn, Michael A; Kapron, James; Mackie, Jennifer; Firth, John; Harrison, Mark; McDougall, Stuart
Background: The determination of pharmacokinetic parameters requires accurate and reliable bioanalytical methods. Even using highly selective MS/MS, interferences can occur. This paper describes the source of some of these interferences with an example discussed involving the problem of a ketamine interference in a plasma assay.Results: The introduction of field asymmetric waveform ion mobility spectrometry (FAIMS) removed the interference, enhanced signal-to-background and met GLP acceptance criteria. Relative to the non-FAIMS method, assay calibration characteristics were improved. The FAIMS source gave optimal performance following the introduction of a split in order to reduce the inlet flow to approximately 0.4 ml/min.Conclusion: The introduction of ion-mobility separation into a bioanalytical LC–MS/MS method can remove unexpected isobaric interferences without the need to redevelop the chromatography.